Nonlineer programlama yöntemlerinden quadratik programlama ile portföy optimizasyonu uygulaması - Yenitepe, Feyzullah (My University, 2000)
One of the most ımportant topics of operatıons research is nonlinear programming (NLP). Many kinds of methods to solve nlp is developıng. Today paralell to the developments in the area of computer and software , nlp solving procedures and methods are always rapidly proceeding. In this master thesis , NLP techniques and solving procedures and aspecially quadratik programming examined. And application is conducted with the use of the datas of İstanbul bond markets (İMKB) 1999 year values. It is made from four chapters. In the first chapter, the quest for optimality , Nonlineer Programming and its mathematical basics conveksity, concavity , gradient vectors and hessian matrix with the NLP's wide variety of using areas collected. In the second chapter, we defined the basic characteristics of nonlinear programming , and explains several useful algorithms employed in solving nonlinear programming problems . In the third chapter , the basics of portfolio selection problem , concepts of efficient portfolios , and portfolio selection system. Each investor is willing to take a certain amount of risk to earn another dollar in returns. In the fourth chapter , application with the datas of İstanbul Bond Markets (İMKB) modelled with the quadratic model and its results collected .
Keywords: Yöneylem Araştırması